The Influence of Lifestyle, Risk Perception, and Ease of Transaction on the Decision to Use Digital Wallet Payment Method is Reviewed in an Islamic Business Perspective : (A Study on DANA Application Users in Bandar Lampung) - Elfany; Zulaikah; Yeni Susanti (International Publisher (YAPENBI), 2025)
This study aims to identify “the influence of lifestyle, risk perception and ease of transaction on decisions using digital wallet payment methods reviewed in the perspective of Islamic Business (study on dana application users in Bandar Lampung). This study uses a quantitative approach. The population in this study are users of the application of funds in the city of Bandar Lampung. Obtained the number of samples of 96.04 rounded to 100 respondents by using the formula unknown population and using purposive sampling techniques. Based on the results of research that has been conducted, it shows that lifestyle, risk perception, and ease of transaction partially have a positive and significant effect on decisions using digital wallet payment methods. Lifestyle, risk perception, and ease of transaction simultaneously have a positive and significant effect on the decision to use the digital wallet payment method on DANA application users in Bandar Lampung City.